Yellow goatsbeard Tragopogon dubius Scop. (Asteraceae): confirmation of its dubious occurrence in Central Slovenia - Nejc Jogan (Natura Sloveniae)
Tragopogon dubius is a species native to SW Slovenia and with several dubious records in central and eastern parts of the country. Its locus classicus is in SW Slovenia at Senožeče, but there is a slight doubt about the type description as no herbarium material has been preserved. All records (and herbarium vouchers in University of Ljubljana’s (LJU) collection) of the species from continental Slovenia have been critically assessed, but none of them has proved to be reliable. Three new recently discovered records linked to the railways in central and E Slovenia are presented and discussed.